Determinan Kinerja Keuangan Perbankan Syariah di Indonesia dalam Perspektif Islam - Amrizal; Isnaldi Muhammad Dini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to test and analyze the influence of the variables Operational Costs, Operational Income, and Financial Deposit Ratio on Non-Performance Financing. To test and analyze Operational Costs and Operational Income and Financial Deposit Ratio to Return on Assets directly or through the Non-Performance Financing variable as a moderating variable. The research object is Islamic banks in Indonesia using secondary data from financial reports from 2017 to 2021. The research design is a quantitative analysis using path analysis. The research results prove that the variables Operational Costs, Operational Income, and Financial Deposit Ratio have a significant positive effect on the Non-Performance Financing variable, the magnitude of the influence is 32.8%. The variables Operational Costs, Operational Income, and Financial Deposit Ratio are proven to have a positive and significant influence on the Return On Assets variable, with the magnitude of the influence being 76%. Based on path analysis, the Operational Cost variable does not affect the On Assets return variable with the Non Performance Finance variable as a moderating variable. Meanwhile, the Financial Deposit Ratio variable influences the return on assets variable with the Non-Performance Finance variable as a moderating variable. Keyword: Financing Ratio, Financial Performance, Financial Report